2016
DOI: 10.3390/genes8010013
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of RNA Editing Sites in the Chloroplast Transcripts of Aegilops tauschii L.

Abstract: RNA editing is an important way to convert cytidine (C) to uridine (U) at specific sites within RNA molecules at a post-transcriptional level in the chloroplasts of higher plants. Although it has been systematically studied in many plants, little is known about RNA editing in the wheat D genome donor Aegilops tauschii L. Here, we investigated the chloroplast RNA editing of Ae. tauschii and compared it with other wheat relatives to trace the evolution of wheat. Through bioinformatics prediction, a total of 34 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…In addition, we compared the RNA editing sites patterns in these plastids, and 15 sites in nine genes were found to be shared by these six Panicoideae cp genomes ( Table 5). It has been proven that the RNA editing was evolutionarily conserved and that species having a closer relationship generally shared more editing sites [45]. In this study, broomcorn millet was found to share 29 editing sites with switchgrass, which was more overlap than for the other four species.…”
Section: Prediction Of Rna Editing Sites In Panicoideae Cp Genomesmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, we compared the RNA editing sites patterns in these plastids, and 15 sites in nine genes were found to be shared by these six Panicoideae cp genomes ( Table 5). It has been proven that the RNA editing was evolutionarily conserved and that species having a closer relationship generally shared more editing sites [45]. In this study, broomcorn millet was found to share 29 editing sites with switchgrass, which was more overlap than for the other four species.…”
Section: Prediction Of Rna Editing Sites In Panicoideae Cp Genomesmentioning
confidence: 55%
“…RNA editing is an important way to regulate gene expression at a post-transcriptional level, which generally changes original genetic information by insertion, deletion, and base substitution of nucleotides within mRNA molecules [44]. Various studies in the chloroplasts of higher plants have suggested that identification of RNA editing sites could be very useful for enriching the genetic information, which makes it easier for organisms to adapt to the environment and also uncover the evolutionary patterns of RNA editing [18,45]. Here, a total of 175 editing sites were predicted in these six Panicoideae cp genomes, and further analysis found that all of these sites were C to U conversions, which was consistent with a previous study of RNA editing in cp genomes in N. tabacum [46].…”
Section: Prediction Of Rna Editing Sites In Panicoideae Cp Genomesmentioning
confidence: 99%
“…Both lead to protein variations ( Table 2, Tables S8-S10), whereas amino acid changes from Alanine to Valine, Histidine to Tyrosine, Leucine to Phenylalanine, Proline to Phenylalanine, Proline to Leucine, Proline to Serine, Arginine to Tryptophan, Threonine to Isoleucine, and Threonine to Methionine result in no physicochemical properties changes in protein. In addition, the Arginine to Cysteine, Serine to Leucine, and Serine to Phenylalanine mutations can modify protein formation due to hydrophilic (Serine and Arginine) to hydrophobic (Leucine, Phenylalanine, and Cysteine) molecule changes [52,53]. Moreover, PREPACT3 has predicted that the genes rps2 and rpl32 can be edited from Glutamine into a Stop codon, and despite they could be polycistronic genes as in other plants [54], these genes are still transcribed according to RNA-Seq data.…”
Section: Discussionmentioning
confidence: 99%
“…RNA editing is a process that occurs in the RNA molecular base change or modification when transcribed, which is one of most important mechanisms regulating gene expression and enriching genetic information at the post-transcription level [50]. A larger number of studies have reported that RNA editing not only controls plant organ formation, growth, and development, but also plays an indispensable role in the response to diverse stresses [51,52]. The RNA-seq data provides a resource to identify the RNA editing sites at the whole transcriptome level.…”
Section: Analysis Of Rna Editing Sitesmentioning
confidence: 99%